Dose regimen for administering glucagon-like peptide 2 (GLP-2) analogs - GLERUP PETER; MORITZEN ULRIKE; SONNY, KIM; JEPPESEN PALLE BECKER (2024)
The present invention relates to dosage regimens for the administration of glucagon-like peptide 2 (GLP-2) analogs. Dosage regimens for administering glucagon-like peptide 2 (GLP-2) analogs and medical uses thereof are disclosed, e.g., for the treatment and/or prevention of gastric and intestinal related conditions and for ameliorating the side effects of chemotherapy and radiotherapy. Dosing regimens for administering glucagon-like peptide 2 (GLP-2) analogs for inducing longitudinal growth of the intestine are described, e.g., for treating patients with short bowel syndrome (SBS). Also described are medical uses for adjusting the volume of a parenteral support (PS) provided to a subject receiving treatment with a GLP-2 analogue in response to the treatment and in response to an algorithm that determines a change in the volume of the PS. 本发明涉及用于施用胰高血糖素样肽2(GLP-2)类似物的剂量方案。公开了用于施用胰高血糖素样肽2(GLP-2)类似物的剂量方案及其医学用途，例如用于治疗和/或预防胃和肠相关病症以及用于改善化学治疗和放射治疗的副作用。描述了用于施用胰高血糖素样肽2(GLP-2)类似物以用于诱导肠的纵向生长的给药方案，其例如用于治疗患有短肠综合征(SBS)的患者。还